Convolvulaceae flora of Shuklaphanta National Park and adjoining areas - Paneru, Dipa; Joshi, Laxmi Raj; Rajbhandary, Sangeeta (Nepal Journal of Botany, 2024)
A short description of the species of family Convolvulaceae of Shuklaphanta National Park and adjoining area of western Tarai Nepal is given in this work. Six genus and sixteen species in total have been documented. Among them, Ipomoea is the most common genera. Ipomoea sagittifolia Burm.fil. is recently added as a record for the flora of Nepal from this area.